2019
DOI: 10.1002/srin.201900376
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Crack Susceptibility of Peritectic Steels Based on Surface Roughness

Abstract: Surface longitudinal cracking during solidification is a serious defect in the continuous casting of peritectic steels, which is dictated by the alloy composition and the cooling rate. Herein, to analyze the crack susceptibility of steels, surface roughness (R a ), which is determined by the peritectic transformation contraction, is proposed to evaluate the cracking tendency of steels. First, the solidified surface roughness of some steels is obtained by a high-temperature laser scanning confocal experiment un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Схильність криць до розтріскування сильно залежить від складу стопу та параметрів процесу виготовлення злитку, таких як швидкість охолодження. В результаті перитектичного перетворення виникає некогерентність меж фаз (до 6%) між δ-феритом та аустенітом; крім того, ці фази мають різну теплопровідність, що сприяє утворенню тріщин під час безперервного лиття [3]. Окрім наведених вище причин, є ще різні пояснення утворення тріщин під час затвердіння криці за безперервного лиття: максимальна термічна усадка зміщується вліво зі збільшенням переохолодження [4]; коли виникає напруження або деформація стиснення затверділої оболонки, що перевищує критичне значення міцности на розрив та інші [1−3].…”
Section: вступunclassified
“…Схильність криць до розтріскування сильно залежить від складу стопу та параметрів процесу виготовлення злитку, таких як швидкість охолодження. В результаті перитектичного перетворення виникає некогерентність меж фаз (до 6%) між δ-феритом та аустенітом; крім того, ці фази мають різну теплопровідність, що сприяє утворенню тріщин під час безперервного лиття [3]. Окрім наведених вище причин, є ще різні пояснення утворення тріщин під час затвердіння криці за безперервного лиття: максимальна термічна усадка зміщується вліво зі збільшенням переохолодження [4]; коли виникає напруження або деформація стиснення затверділої оболонки, що перевищує критичне значення міцности на розрив та інші [1−3].…”
Section: вступunclassified
“…Based on the phase diagram of the Fe-C alloy, influence of alloy elements, and continuous cooling process, the pseudobinary phase diagram of the steel used in this experiment was drawn using the Factsage software, [12,14,18] as shown in Figure 7a. It can be seen that the temperature of peritectic transformations is lower than T Perit , and the starting and ending temperatures of the peritectic reaction are not the same, which are 1493 and 1448 C, respectively.…”
Section: Relationship Between Corner Cracks and Solidification Characteristics Of Steelmentioning
confidence: 99%
“…[16,17] Uneven solidified billet shells and mismatches in the contraction coefficients lead to the accumulation of stress. [18] When the stress sustained by the billet is greater than the ultimate stress it can withstand, microcracks will form in the billet. [19] In this study, the causes of the cracks in the corners of the hypoperitectic microalloyed steel billet are analyzed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the surface roughness of the peritectic steels was higher and the surface roughness changed with cooling rate. [19] The surface roughness however may not predict shell thinning that could lead to a catastrophic break-out during continuous casting of steels. In other words, complete thickness measurement of the entire surface area of the shell could be necessary.…”
Section: Shell Thickness Measurementsmentioning
confidence: 99%